Enhancing the in vitro anticancer activity of albendazole incorporated into chitosan-coated PLGA nanoparticles. (1st March 2017) - Kang, Bong-Seok; Choi, Jin-Seok; Lee, Sang-Eun; Lee, Joon-Kyung; Kim, Tae-Hyeon; Jang, Woo Suk; Tunsirikongkon, Amolnat; Kim, Jin-Ki; Park, Jeong-Sook
Graphical abstract: Abstract: To improve the solubility and anticancer activity of albendazole (ABZ), chitosan (CS)-coated poly- dl -lactic-co-glycolic acid (PLGA) nanoparticles were developed. CS was used to coat ABZ-loaded PLGA nanoparticles to enhance both mucoadhesiveness and colloidal stability. CS-coated PLGA nanoparticles were prepared by suspending the nanoparticles in CS solution after solvent diffusion. The CS-coated PLGA nanoparticles were characterized, and ABZ release was studied in vitro from various formulations. The mucoadhesive properties and in vitro anticancer activities of CS-coated PLGA nanoparticles were investigated by measurement of zeta potentials and the MTT assay, respectively. Spherical nanoparticles below 500 nm in diameter were successfully prepared; the particle size distribution was narrow. Complete encapsulation of ABZ in CS-coated PLGA nanoparticles was confirmed by SEM, FTIR, DSC, and XRD. The particle sizes of CS-coated PLGA nanoparticles were in the range of 260–480 nm; the encapsulation efficiency was 43.4–54.6%; and the yield 58.5–67.8%. The zeta potential of CS-coated nanoparticles was above +27 mV and stability was maintained for 4 weeks. At pH 7.4, the in vitro release of ABZ from nanoparticles (P188-5) was 200-fold higher than that from untreated ABZ; this persisted for 12 h. Moreover, ABZ release from CS-coated PLGA nanoparticles (P188-CS0.5) was 1.5-fold higher than that from untreated ABZ at pH 1.2. Additionally, the ABZ-loaded CS-coated nanoparticles exhibited superior mucoadhesion and improved cytotoxicity. The results show that CS coating of PLGA nanoparticles may improve the anticancer effect and the mucoadhesive properties of ABZ-loaded nanoparticles.